Dekonstruksi Pemaknaan Mualaf Sebagai Penerima Zakat di Indonesia - Akmal Bashori; Sugitanata, Arif; Karimullah, Suud Sarim (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2024)
This article addresses the underexplored issue of the neglect faced by Mualaf as zakat recipients post-prophethood, necessitating a contemporary deconstruction of the concept. The objective is to ensure that, despite editorial disparities, the essence of Mualaf aligns with fiqh mainstream. The method involves applying Jaques Derrida's deconstruction theory in a qualitative research framework. The results reveal that the deconstruction of contemporary Mualaf primarily intersects with praxis, emphasizing the awakening of individuals' hearts to rediscover their inherent human nature inclined towards goodness. The implications point to a reconstructed understanding of Mualaf, manifested in practical initiatives such as efforts to revive those ensnared in immoral activities, support mental rehabilitation for individuals affected by addiction, and contribute to the development of isolated communities or tribes in remote areas. This study sheds light on the transformative potential of reevaluating Mualaf in addressing societal challenges and advocates for a nuanced understanding in the discourse surrounding zakat recipients